MODERN INSTRUMENTAL METHODS TO CONTROL THE SEED QUALITY IN ROOT VEGETABLES - F. B. Musaev; A. F. Bukharov; E. G. Kozar; S. L. Beletskiy (Овощи России, 2017)
The standard methods of analysis don’t meet all modern requirements to determine the seed a quality. These methods can’t unveil inner deficiencies that are very important to control seed viability. The capabilities of new instrumental method to analyze the seed quality of root vegetables were regarded in the article. The method of micro-focus radiography is distinguished from other existing methods by more sensitivity, rapidity and easiness to be performed. Based on practical importance the visualization of inner seed structure, it allows determining far before seed germination the degree of endosperm development and embryo; the presence of inner damages and infections, occupation and damage caused by pests. The use of micro-focus radiography enables to detect the degree of seed quality difference for some traits such as monogermity and self-fertilization that are economically valuable for breeding program in red beet. With the aid of the method the level of seed development, damage and inner deficiencies in carrot and parsnip can be revealed. In X-ray projection seeds of inbred lines of radish significantly differed from variety population ones for their underdevelopment in the inner structure. The advantage of the method is that seeds rest undamaged after quality analyzing and both can be used for further examination with the use of other methods or be sown; that is quite important for breeders, when handling with small quantity or collectable plant breeding material. The results radiography analyses can be saved and archived that enables to watch for seed qualities in dynamic; this data can be also used at possible arbitration cases.